Could microalgae offer promising options for climate action via their agri-food applications? - Siedenburg, Jules (Frontiers in Sustainable Food Systems, 2022)
In 2021 the Intergovernmental Panel on Climate Change (IPCC) issued the first volume of its latest authoritative report on climate change. Underlining the seriousness of the situation, the United Nations Secretary-General branded its findings a “code red for humanity.” The need for climate action is now evident, but finding viable pathways forward can be elusive. Microalgae have been attracting attention as a category of “future food,” with species like Arthrospira platensis (spirulina) and Chlorella vulgaris (chlorella) seeing growing uptake by consumers while research interest continues to expand. One timely but neglected question is whether microalgae might offer options for promising climate actions via their agri-food applications. Specifically, might they offer scope to help secure food supplies, while also providing climate resilient livelihood pathways for vulnerable farmers already grappling with food insecurity and environmental degradation? This paper reports on a review of the academic literature on microalgae as an agri-food technology, notably their uses as a food, feed, biofertilizer, biostimulant, and biochar. This family of applications was found to offer promising climate actions vis-à-vis both mitigating and adapting to climate change. Aspects pertinent to adaptation include growing rapidly under controlled conditions, reusing water, providing potent nutrition for humans and animals, and supporting resilient crop production. Agri-food applications of microalgae also provide opportunities to mitigate climate change that could be explored. The paper concludes by flagging possible risks and obstacles as well as research and policy priorities to elaborate and harness this potential.